Pengaruh Profitabilitas dan Tingkat Utang Perusahaan terhadap Tarif Pajak Efektif - Haryanto, Felicia; Keristin, Usnia Wati (Universitas Multi Data Palembang, 2024)
This study aims to obtaining empirical to the impact of profitability and company debt level on the effective tax rates of food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the period 2019-2022. The study population consists of 88 companies and 17 companies with 68 total observations for 4 years was selected by using purposive sampling method. The findings indicate that neither the profitability variable nor company debt level demonstrates any significant impact on the effective tax rates by using T-test. In contrast, both variables demonstrate significant and simultaneous effects on the effective tax rates by using F-test.